Uptake and dissemination pathways for climate-smart agriculture technologies and practices in Lushoto, Tanzania - Nyasimi, Mary; Radeny, Maren A.O.; Kimeli, Philip; Mungai, Catherine; Sayula, George; Kinyangi, James (2016)
Smallholder farmers in East Africa need information and knowledge on appropriate climate-smart agriculture (CSA) technologies and practices, and institutional innovations in order to effectively adapt to climate change and cope with climate variability. This paper assesses farmer uptake of climate-smart agricultural practices and innovations following a farmer learning journey through the Farms of the Future (FotF) approach. First, we explore and assess the various CSA technologies and practices, including institutional innovations farmers are using. Second, we identify and document farmer learning and dissemination pathways that can enhance uptake of CSA technologies and practices. Third, we identify existing institutions that can enhance uptake of CSA practices. We use household survey data, complimented with qualitative information from focus group discussions and key informant interviews. The results show farmers are using a variety of CSA technologies and practices, and institutional innovations. Improved crop varieties, agroforestry, and scientific weather forecast information were cited as the main CSA practices used. To minimize their risks and reduce vulnerabilities, farmers are diversifying and integrating five to ten practices in one season. Matengo pits, Savings and Credit Cooperative Organization (SACCOs) and energy efficient cook stoves were used by very few farmers due to high initial investment costs and unsuitability to the area. Over 95% of the farmers reported receiving agricultural information orally from a variety of sources including government extension workers, seed companies, researchers, traditional experts, neighbors, radio agricultural shows, religious groups, farmer groups, and family members. Farmers acknowledged the FotF approach as a useful tool that enabled them to interact with other farmers and learn new CSA practices and innovations.